Study of submerged arc welding using inverter power source / Mazlan Md Suki, Norhisham Launah and Rustam Affendy Abd Rahim - Md Suki, Mazlan; Launah, Norhisham; Abd Rahim, Rustam Affendy (1997)
Welding is defined as the intimate joining of metals where incoalescence is produced by heating to suitable temperatures, with or without the use of either pressure or filler metal. Welding is important in the light of: i- Replacing casting. ii- Replacing riveting. iii- Only technique of fabrication. iv- Specially developed processes for new materials. v- Its sales value. Welding is not just a matter of adding enough heat to a melt it and then letting its solidify. The strength and the integrity of a weld depend on the material properties of the metal being welded, as weld as on a great main others factors. These factors include the shape of the weld, the temperature of the heat source and even the type of power source on the weld. Many of these factors are the same for all welding and cutting process.